Women on boards and firm performance in Malaysia - post implementation period - Ahmad, Maslina; Abdirahman, Sadik; Annuar, Hairul Azlan (2020)
In 2011, the Malaysian Cabinet approved a policy that by 2016, the board of directors of all public listed companies in Malaysia should consist of at least 30% women. This research examines the relationship between the existence of women on boards and Malaysian listed companies’ performance after the effective implementation of the policy. This research also examines the qualifications of women directors, women directors on audit committees, women directors as CEOs or Chairman, their age, tenure and independence. All of these features are examined in relation to return on assets (ROA). The study utilises resource dependence theory as the basis to explain the relationship between women on boards and firm performance. To achieve the research objectives, the annual reports of the top 100 public listed companies from 2016 to 2018 are examined using panel data analysis. The results show that there is a significant positive curvilinear relationship between women on boards and firms’ financial performance. When examining women in audit committee, it is found that there is a significant negative curvilinear relationship with firm performance. Furthermore, this study finds that there is a significant positive relationship between women as CEOs or Chairman and firm performance. This research contribute to the existing literature on women on boards from the perspective of a developing nation. The results could motivate listed firms in Malaysia to appoint more qualified women as members of the boards in order to not only adhere to the government policy but also gained benefits in term of company performance.